Fuzzyfication Optimization of Crude Cassava Starch Processing into Tapioca Flour with the Mamdani Approach - Bintang Aprilio; Fionando Emir Satriadana; Muhamad Raihan Afarel Nadji Baraba; Nourma Ayuadika; Refiansyah Nur; Sesar Husen Santosa; Muhammad Danang Mukti Darmawan; Nanda Octavia (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
The purpose of this research is to improve the effectiveness of tapioca flour production by using a fuzzy logic system. The system accepts three variables, namely raw materials, color, and aroma, and produces an output in the form of a percentage of the quality of tapioca flour produced. Fuzzy rules are created based on expert knowledge and experimental data after the input data is converted into fuzzy values. MATLAB software is used to implement the fuzzy system. Furthermore, the simulation results were analyzed to find the best conditions for producing tapioca flour with high quality. The results show that the fuzzy system successfully produces an output that reflects the quality percentage of tapioca flour. However, to gain a more complete understanding, it is necessary to further analyze the components that affect production quality, and there may be better ways to customize the fuzzy rules.